Impact of urban child labor in the health of children and adolescents - Ana Claudia Martins; Débora Pastore Bassitt; Kátia da Silva Wanderley; Mayra dos Santos Silva (Universidade de Fortaleza, 2013)
Objective: To analyze the health of children and adolescents who are under workingconditions in São Paulo. Methods: The study considered 32 children and adolescents,aged between 6 and 14, enrolled on the Child Labor Eradication Program (Programa deErradicação do Trabalho Infantil - PETI, Brazil) from three different regions of the city ofSão Paulo. The participants were individually assessed through an occupational anamnesis,systematized by an evaluation form, to collect data on labor activity and Lipp & Lucarelli'sChild Stress Scale was applied. Data statistical analysis was performed with softwaresEVOC 2000 and SPSS. Results: It was found that recycling was the predominant occupation,totalizing 59.3% of the sample, and the collective method was more prevalent in relationto the individual one. Over 90% of participants used protective equipment in workingactivity and 72% do not miss the occupation they once had. Of the participants presentingsignificant signs of stress, 75% work or used to work with recycling activities and 87.5% arestill engaged on the activity. When analyzing the Child Stress Scale, it was noted that thereare more stress signs in child workers (46.7%) in comparison to the former workers (5.9%)and significant difference between work and stress (p-value 0.008). Conclusions: It wasnoted that the labor activity in childhood may cause perturbation ofpsychophysiological nature and, in spite of the relatively small sample size, deleterious aspects of this activityfor children and adolescents were pointed out. It was also evidenced that, despite a highpercentage of this group becomes enrolled on the program, they still keep their occupation.